Pengaruh Pengetahuan, Ketrampilan, Kemampuan, Sikap, Perilaku terhadap Produktivitas - Asmuni Asmuni; Tantri Widiastuti (STIE Widya Manggala, 2012)
The purpose of this study was to find out the influence of knowledge, skills, abilities, attitudes and behaviors on productivity of the employees of the production department of PT Lukie Works Indonesia. The population in this study was 358 employees of the production department of PT Lukie Works Indonesia. While the samples were 80 respondents. The sampling technique used was non probability sampling with Judgment. The analysis tool used in this research was multiple linear regression, which was firstly examined by validity and reliability test. The results partially showed that there was significant influence of knowledge, skills, abilities, attitudes and behaviors on productivity of theemployees of the production department of PT Lukie Works Indonesia. While the hypothesis test simultaneously with the test results obtained was significant influence of knowledge, skills, abilities, attitudes and behaviors on productivity of the employees of the production department of PT Lukie Works Indonesia. The coefficient of determination of the five independent variables = 66.3% meaning that the variation of the five independent variables in explaining productivity = 66.3% while the remaining 33.7% was explained by other variables that were not mentioned in this study.